2006
DOI: 10.1139/x06-012
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of green foliage in eastern hemlock forests of southern New England impacted by hemlock woolly adelgid infestations

Abstract: This study examined the impacts of hemlock woolly adelgid (Adelges tsugae Annand) (HWA), a small, invasive insect, on foliar chemistry, forest floor microclimate, and subsequent green foliage decomposition in eastern hemlock (Tsuga canadensis (L.) Carrière) forests. We investigated the direct effects of HWA feeding and indirect changes in microclimate on foliar decomposition by incubating HWA-infested and uninfested foliage across eight eastern hemlock dominated stands in southern New England that had differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 53 publications
0
38
1
Order By: Relevance
“…Th ey suggested that decreases in the forest fl oor mass could have resulted from greater decomposition rates in HWA-infested stands due to changes in environmental variables or litter quality. Cobb et al (2006) found that aft er 120 d of decomposition, foliage from infested trees had a greater N concentration and lower C/N ratio than foliage from uninfested trees, suggesting N immobilization. We expect the decline in hemlock foliage inputs with hemlock mortality (Fig.…”
Section: Nutrient Poolsmentioning
confidence: 95%
“…Th ey suggested that decreases in the forest fl oor mass could have resulted from greater decomposition rates in HWA-infested stands due to changes in environmental variables or litter quality. Cobb et al (2006) found that aft er 120 d of decomposition, foliage from infested trees had a greater N concentration and lower C/N ratio than foliage from uninfested trees, suggesting N immobilization. We expect the decline in hemlock foliage inputs with hemlock mortality (Fig.…”
Section: Nutrient Poolsmentioning
confidence: 95%
“…In forest stands of the cove forests in the southern part of its range, in mixed forests of New England and southern Canada, and along riparian corridors throughout its >10,000 km 2 range, eastern hemlock can account for >50% of the total basal area [17,23]; see [2,[24][25][26] for detailed discussions of the foundational role of eastern hemlock in stands where it is the dominant species. The forest floor beneath the eastern hemlock canopy is cool and dark [16,27], and the slowly decomposing hemlock needles give rise to a deep organic layer, which is very acidic and low in nutrients [28]. Unique faunal assemblages, including groups of birds [29], arthropods [30][31][32], and salamanders [33] live in eastern hemlock stands.…”
Section: Eastern Hemlockmentioning
confidence: 99%
“…air temperatures are above freezing, but photosynthetic rates are slow, water-use efficiency is high, and peak carbon fixation by T. canadensis occurs in spring and fall, not in the summer when cooccurring broadleaved, deciduous trees are in full leaf [16]. Because the needles of T. canadensis are slower to decompose than all of the other regionally cooccurring trees [17], organic matter accumulates unusually rapidly beneath T. canadensis canopies [18], but the soils are acidic and nutrientpoor [19]. Overall, both carbon flux [16,[20][21][22][23] and nutrient cycling [19,[24][25][26] are much slower in T. canadensis stands than in stands dominated either by hardwoods or other conifers.…”
Section: Introductionmentioning
confidence: 99%